Cash flow sensitivity of investment: Evidence from the Polish listed companies - Marian Nehrebecki (Central European Economic Journal (CEEJ), 2020)
The paper focuses on assessment of the sensitivity of investment on cash flow (ICFS) made by listed companies in Poland. Achieving this goal will also involve analysing and drawing conclusions about the balance-sheet channel of monetary transmission. An empirical part uses data from financial statements for Poland derived from Emerging Markets Information Services (EMIS), related to companies listed on the Warsaw Stock Exchange and NewConnect. Estimations were made using the Ordinary Least Squares method with robust standard errors, and results made it clear that cash flow has a positive significant impact, indicating that most companies operate on the imperfect and incomplete market, and with constrained or costly access to external financing. Further, it is found that the impact is significantly strong in the slowdown, as financial constraints are more binding. These results seem to confirm that the balance-sheet channel of monetary transmission is operative in Poland.
Keywords: C33; E22; E44; 330; investment; cash flow; ICFS; balance sheet channel; financial accelerator